2014
DOI: 10.1007/s13204-014-0300-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro, in vivo and pharmacokinetic assessment of amikacin sulphate laden polymeric nanoparticles meant for controlled ocular drug delivery

Abstract: The rationale of current exploration was to formulate positively charged amikacin-loaded polymeric nanoparticles providing a controlled release attribute. Amikacin sulphate-loaded nanoparticles were prepared by w/o/w emulsification solvent evaporation approach succeeded by high-pressure homogenization. Two bioadhesive positively charged polymers, Eudragit Ò RS 100 and Eudragit Ò RL 100, were used in the blend, with variable ratios of drug and polymer. The formulations were assessed in terms of particle size an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…This fit suggests that gentamicin release from the SiO 2 -gentamicin nanohybrids is controlled by Fickian diffusion [20,22]. Nevertheless, the release data fit fairly well to first-order model (Figure 6B) with R 2 value of 0.9655; this can explain the initial fast release of gentamicin during the first 24 h. Previous studies have reported that fitting quality is likely better for the initial stage than for the terminal one [24].…”
Section: Resultsmentioning
confidence: 66%
“…This fit suggests that gentamicin release from the SiO 2 -gentamicin nanohybrids is controlled by Fickian diffusion [20,22]. Nevertheless, the release data fit fairly well to first-order model (Figure 6B) with R 2 value of 0.9655; this can explain the initial fast release of gentamicin during the first 24 h. Previous studies have reported that fitting quality is likely better for the initial stage than for the terminal one [24].…”
Section: Resultsmentioning
confidence: 66%
“…Among these, Ag-NPs have unique optical, electrical and biomedical properties, making them suitable for biosensing, imaging and catalysis, as medicine and in nano device fabrication and drug delivery (Ismail et al 2017;Lee and El-Sayed 2006;Nair and Laurencin 2007;Upendra et al 2015). There is a growing demand to develop eco-friendly methods, which are free from toxic substances, for the synthesis of NP (Lade and Patil 2017;Smetana et al 2005;Yu 2007;Zhang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These results were attributed to the enhanced drug retention at the eye surface due to the encapsulation of the drugs in the nanoparticles, and a progressive and continuous release of the incorporated drugs from the nanoparticles adhered on the cornea surface [151, 152]. Amikacin loaded EUDRAGIT ® RS 100/RL 100 nanoparticles were prepared and assessed for in vitro , in vivo and pharmacokinetic performances [163]. They had a mean particle size 122–242 nm, and zeta potential 29–46 mV depending on the proportion between RS 100 and RL 10.…”
Section: Nanoparticles For Drug Delivery To the Anterior Segmentmentioning
confidence: 99%
“…In vivo ocular retention study by scanning electron microscope revealed that the EUDRAGIT ® nanoparticles exhibited corneal adherence for prolonged 6 h after instillation in healthy male albino rabbits. The EUDRAGIT ® nanoparticles significantly increased the C max ~1.733 times and AUC 0–12 h ~2.12 times of amikacin in aqueous humor more than the commercial ophthalmic solution of amikacin sulfate [163]. Hybrid EUDRAGIT ® nanoparticles were prepared using o/w emulsification-solvent evaporation method from mixtures of PLGA and EUDRAGIT ® RL with different weight ratios (75:25, 50:50 and 25:75) [139].…”
Section: Nanoparticles For Drug Delivery To the Anterior Segmentmentioning
confidence: 99%